2009
DOI: 10.1159/000232493
|View full text |Cite
|
Sign up to set email alerts
|

Forearm Length – A New Tool to Standardize Bone Parameters of the Forearm Measured with Peripheral Quantitative Computed Tomography in Individuals with Disproportional Growth of Forearm Length and Body Height

Abstract: Aim: To investigate the relationship of forearm length (FL) or height to bone parameters of the forearm of a normal pediatric population in comparison to individuals with osteogenesis imperfecta (OI). Methods: Data on FL, height and peripheral quantitative computed tomography measurements of the forearm were collected from participants of the DONALD study (140 males and 156 females; age 5–19 years) and from 73 patients with OI (53 males; mean age ± SD: 11.7 ± 3.3 years). Bone mineral content (BMC) was transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For example, a high sitting height to height ratio (or low upper/lower segment ratio) is suggestive of skeletal dysplasia and an excessively high extremities to trunk ratio implies disproportionately short trunk, such as spina epiphyseal dysplasia . A low arm span and short forearms are suggestive of a defect in the SHOX gene . Interestingly, the difference in height among different socio‐economic classes are primarily because of increase in leg length and not an increase in sitting height and prior studies have found a strong correlation between lower segment measurements and height …”
Section: Discussionmentioning
confidence: 99%
“…For example, a high sitting height to height ratio (or low upper/lower segment ratio) is suggestive of skeletal dysplasia and an excessively high extremities to trunk ratio implies disproportionately short trunk, such as spina epiphyseal dysplasia . A low arm span and short forearms are suggestive of a defect in the SHOX gene . Interestingly, the difference in height among different socio‐economic classes are primarily because of increase in leg length and not an increase in sitting height and prior studies have found a strong correlation between lower segment measurements and height …”
Section: Discussionmentioning
confidence: 99%
“…Data on the individual professions of the participants are not available. For more information on the study please see http://www.fke-do.de and the publications of Schoenau et al, (; see also Rauch et al, ; Fricke et al, ). Due to study design, only the radius and the muscle cross‐sectional area of the nondominant forearm were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Even though it is today common to standardize cortical bone properties of the lower limbs by the product of body mass and bone length (following Ruff, ), the most appropriate method of standardization is still under debate (Trinkaus and Ruff, ). However, while there is strong evidence that for weight bearing limbs standardization by body mass is the best method so far (Ruff et al, ), it has been demonstrated that muscle and bone properties of the radius are not significantly influenced by weight (Fricke et al, ). In medicine, pQCT values are often standardized by forearm length (see, e.g., Fricke et al, ) or stature (see, e.g., Schoenau, ; Schoenau and Fricke, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations